Genetic Variation For Grain Zinc And Iron Concentrations And Quality Parameters In Wheat (Triticum Aestivum L.) Genotypes (Applied Biological Research, 2017)
Grains of fifty lines of bread wheat (Triticum aestivum L.) representing diverse  genotypes were analyzed in the year 2015 for variation in their micronutrient  concentrations. Both grain Zn and Fe concentrations correlated negatively  with grain yield and 1000-grain weight. Zn concentration also correlated  significantly but negatively with phenol reaction score and plant height. Grain  Fe concentration correlated significantly but positively with plant height,  grain Zn and grain protein concentration. However, the correlations of Fe  content with days to heading, grain appearance score, sodium dodecyl  sulphate (SDS) sedimentation value and phenol reaction score and  correlations of Zn content with days to heading, grain appearance score, SDS  and grain protein were weak. Both Fe and Zn concentration showed negative  direct on grain yield. Significant differences between bread wheat genotypes  were found for grain Fe and Zn concentrations. Five entries namely 448, 412,  420, 414 and 419 showed high values for both Fe and Zn concentration. For  Zn, an increment of 33.3% (54.4 ppm) over check (40.8 ppm) was observed.  For Fe, an increment of 28.1% (45.1 ppm) was observed over check (35.2  ppm). The information generated could be used for developing micronutrient  biofortification strategies.
Keywords: Biofortification; grain protein; iron; yield; zinc